2001
DOI: 10.1007/s003300000668
|View full text |Cite
|
Sign up to set email alerts
|

Gadolinium-enhanced MR angiography of the breast: Is breast cancer associated with ipsilateral higher vascularity?

Abstract: The aim of this study was to assess a possible association between breast malignancy and ipsilateral higher vascularity on gadolinium-enhanced MR angiography. One hundred six patients were examined by dynamic gadolinium-enhanced 3D MR imaging. Magnetic resonance angiographic views were generated by image subtraction and maximum intensity projection. The study included 85 patients with unilateral malignant breast neoplasms and 21 with unilateral benign lesions. Three blinded readers independently reviewed the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 9 publications
2
46
1
1
Order By: Relevance
“…MRI also enables assessment of ipsilateral vascularity as a whole and observation of increased vascularity in cancerbearing breasts, which could be used as a sign of malignancy [17][18][19]. Mahfouz et al [18] showed an association between breast cancer and a higher ipsilateral vascularity; however, the sensitivity and specificity of this sign for the diagnosis of malignancy were only 76.5% and 57%, respectively. Sardanelli et al [17] suggest that vascular asymmetry could be considered a potential MRI sign of invasive breast cancer, with sensitivity and specificity of 88% and 82%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MRI also enables assessment of ipsilateral vascularity as a whole and observation of increased vascularity in cancerbearing breasts, which could be used as a sign of malignancy [17][18][19]. Mahfouz et al [18] showed an association between breast cancer and a higher ipsilateral vascularity; however, the sensitivity and specificity of this sign for the diagnosis of malignancy were only 76.5% and 57%, respectively. Sardanelli et al [17] suggest that vascular asymmetry could be considered a potential MRI sign of invasive breast cancer, with sensitivity and specificity of 88% and 82%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although ipsilateral increased vascularity is frequently associated with ipsilateral invasive breast cancer, the question of whether this finding is clinically valuable remains largely unanswered. Indeed, intermediate sensitivity and specificity, which have been described in earlier MRI studies, make it less reliable in individual patients [17,18]. Therefore, additional study should be focused on differentiation of benign breast lesions or no lesions.…”
Section: Mdct Of Whole-breast Vascularitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, some reports suggest that preoperative breast MRI in women with newly diagnosed cancer could potentially increase the rate of unnecessary biopsies and surgery [2]. Recent studies aimed to increase the specificity of breast DCE-MRI by adding a vessel analysis to the standard morphologic and kinetic criteria, therefore exploring the diagnostic value of vascularity [7][8][9]. During the past decade, this research issue has been approached in two ways: first, whole-breast vascularity, and second, local vascularity, that is, vessels adjacent to and feeding a lesion or lesions [9].…”
Section: Description Of Purposementioning
confidence: 99%